A Case Report: Euglycemic Diabetic Ketoacidosis Presenting as Chest Pain in a Patient on a Low Carbohydrate Diet - Dorcely, Brenda (Curr Diabetes Rev, 2021)
INTRODUCTION: Sodium-glucose cotransporter-2 [SGLT2] inhibitors reduce cardiovascular events and mortality in patients with diabetes, particularly patients with established cardiovascular disease. Euglycemic diabetic ketoacidosis [euDKA], a complication of SGLT2 therapy, can be exacerbated by a low carbohydrate diet. CASE REPORT: A 61-year-old man with a history of type 2 diabetes, taking an SGLT2 inhibitor empagliflozin 10 mg orally daily, presented to the emergency room with a 2-day history of nausea and chest pain. A week prior to presentation, he had started a ketogenic diet. He was initially admitted with a diagnosis of acute coronary syndrome. On initial assessment in the emergency room, his cardiac enzymes were normal and there were no ischemic changes in his ECG. As there was concern for unstable angina, he underwent cardiac catheterization, which showed a known total occlusion with collaterals and arteries with a non-obstructive disease without any evidence of acute plaque rupture. His baseline laboratory assessments revealed an elevated anion gap of 17, increased urinary and plasma ketones, and metabolic acidosis. His plasma glucose level was 84 mg/dL. The diagnosis of euDKA was made, and treatment with intravenous fluids and insulin was initiated. His chest pain and nausea subsequently resolved. CONCLUSION: We present a case of euDKA triggered by a ketogenic diet while on SGLT2 inhibitor therapy presenting as chest pain. The recognition of euDKA is important in the context of increased SGLT2 use for the management of cardiovascular risk for patients with diabetes.